PENGARUH VARIASI KECEPATAN PUTARAN DAN KEDALAMAN PEMOTONGAN BENDA KERJA BAJA S45C TERHADAP KEKASARAN PERMUKAAN PROSES GERINDA SILINDRIS - Mahendra Saputra Indra; Muhamad Riva’i; Husman Husman (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
The result of minimal surface roughness is the desired result in the machining process of the JAINNHER Cylindrical Grinding Machine type JHU-3506H No.3506H006, because the cylindrical grinding machining process is included in the advanced machining process in the field of finishing. This study aims to obtain the smallest roughness value and what percentage of the influence of each parameter on the surface roughness of the cylindrical grinding machining process. The machining process parameters that were varied were the workpiece rotation speed with parameters 66 rpm, 100 rpm, and 158 rpm to the depth of cutting with parameters 0.015 mm, 0.020 mm, and 0.025 mm. The optimization method used is Taguchi. The experimental design was determined based on the Taguchi method and was in the form of an orthogonal matrix L9 (3^2). The experiment was carried out randomly with 1 replication to overcome the disturbance factor that occurred during the machining process. From the research that has been done, the results obtained show that to obtain a minimum surface roughness of the workpiece, the rotation speed of the workpiece is set at 66 rpm with a feeding depth of 0.015 mm. And to reduce the variation of the response simultaneously, the rotational speed of the workpiece has a contribution of 12.0625% and the depth of cutting has the largest contribution, which is 83.8622%.